Tailoring the Structural Evolution of Multi‐Electron Redox Conversions via Strong Selenium–Carbon Interaction for Robust Aqueous Copper‐Ion Batteries - Fan Jiang; Haoyu Peng; Yiqian Wu; Yichen Li; Zeyu Zhang; Yue Wang; Jiuqiang Li; Jing Peng; Maolin Zhai (Advanced Science)
Abstract Aqueous metal‐selenium batteries based on chalcogenide cathodes, despite their multi‐electron conversion‐type redox reactions and rapid kinetics, suffer from short lifespans and unclear capacity degradation mechanisms. The interfacial interactions between doped carbon and chalcogenides correlate closely with the electrochemical structural evolution. Hence, flower‐like Cu2−xSe wrapped with ultrathin N‐doped carbon layer (Cu2−xSe@N‐C) is synthesized via a simple γ radiation‐pyrolysis route for the first time. The Cu2−xSe@N‐C cathode displays a high‐rate performance and long‐term stability, with a respective capacity of 310.6 mAh g−1 at 20 A g−1 and a capacity retention rate of 92.9% after 30 000 cycles over 2000 h at 5 A g−1. Ex situ X‐ray diffraction and X‐ray photoelectron spectroscopy confirm the reversible Cu storage mechanism of the Cu2−xSe@N‐C cathode and the issues of volume expansion and oxidative dissolution related to the capacity degradation of the Cu2−xSe cathode. Furthermore, X‐ray absorption analysis and theoretical calculations reveal the presence of Se─C interactions between the ultrathin N‐doped carbon and Cu2−xSe. As a result, the physical and chemical dual‐protection of N‐doped carbon via Se‐C not only effectively stabilizes the structural evolution of Cu2−xSe but also endows it with faster electrode reaction kinetics.